2016
DOI: 10.1080/09205063.2016.1196531
|View full text |Cite
|
Sign up to set email alerts
|

Photo-induced in situ crosslinking of polymer brushes with dimethyl maleimide moieties for dynamically stimulating stem cell differentiation

Abstract: We designed photo-crosslinkable polymer brushes with dimethylmaleimide moieties, in order to demonstrate dynamic stimulation of cell differentiation in mesenchymal stem cells (MSCs). The polymer brushes were synthesized by surface-initiated reversible addition fragmentation chain transfer polymerization using dimethylmaleimide ethyl methacrylate and methyl methacrylate on a chain transfer agent-immobilized glass surface. The polymer brushes were crosslinked by photodimerization of the dimethylmaleimide moietie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Maleimide conjugation has been utilized in protein nanoparticle vaccine formulations. [ 48,49 ] Jones et al [ 48 ] demonstrated a method to produce protein vaccine nanoparticles using malarial antigens via maleimide modification and thiolation. Pfs25M, AMA1, CSPM3 antigens from P. falciparum were conjugated separately using SATA (N-succinimidyl S-acetylthioacetate), which added sulfhydryl groups on each lysine via N-hydroxysuccinimide (NHS) ester conjugation.…”
Section: Maleimide Conjugationmentioning
confidence: 99%
“…Maleimide conjugation has been utilized in protein nanoparticle vaccine formulations. [ 48,49 ] Jones et al [ 48 ] demonstrated a method to produce protein vaccine nanoparticles using malarial antigens via maleimide modification and thiolation. Pfs25M, AMA1, CSPM3 antigens from P. falciparum were conjugated separately using SATA (N-succinimidyl S-acetylthioacetate), which added sulfhydryl groups on each lysine via N-hydroxysuccinimide (NHS) ester conjugation.…”
Section: Maleimide Conjugationmentioning
confidence: 99%
“…While there are few examples of using cross-linker based strategies such as using photochemically induced radical thiol–ene reaction, , utilization of single-component photochemical cross-linking strategies for nanofibers is quite rare. Most reports of cross-linking of polymeric materials employ polymers bearing acrylate, methacrylate, and methacrylamide groups, cinnamates, benzophenones, uracil, and dimethylmaleimides. While most reports utilize the dimethyl maleimide derivative, utilization of unsubstituted maleimide group provides avenue for post-cross-linking functionalization using the residual maleimide units. Recently, we reported that it is possible to fabricate cross-linked hydrogels from polymeric precursors containing maleimide groups .…”
Section: Introductionmentioning
confidence: 99%